PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK - Sari, Lili Nur Indah (IAIN PADANGSIDIMPUAN, 2017)
Increasing the Ability of Problem Solving by Using Realistic Mathematics Education approach (RME) in Seventh Year Student Class. The aims of the research are: (1) to know the increasing ability of problem solving mathematic student’s by using Realistic Mathematics Education approach, (2) to know there was the interaction between learning and first mathematic ability toward the increasing ability of problem solving mathematic. The research was carried out at MTs S Al-Hijrah Medan. The population of this research is the student grade 1 (one) by taking a sample of the two classes. The data obtained through test THURS, test the ability of mathematical problem solving. The data was analyzed with the test of ANAVA two lines. The result of this research shown that (1) there was increasing ability in problem solving mathematic student’s by using Realistis Mathematics Education approach was better than using direct struction, (2) there were no interaction between learning and student’s ability level to the increasing ability of problem solving mathematic. Research findings recommend RME approach was made one of the learning approaches used in primary schools to conduct varied and innovating learning.